Análisis Estadístico De Los Residuos Sólidos Domésticos De La Parroquia San Sebastian Del Coca Del Cantón Joya De Los Sachas - Pazmiño, Juan Pablo Wayllas; Arévalo, Luis Fabián Cabezas (European Scientific Journal, ESJ, 2018)
A statistical analysis was carried out on the characterization of domestic solid waste that was generated in the San Sebastian del Coca parish which belongs to the Canton Joya de los Sachas. This paper focuses on quantifying the generation of solid waste, calculating the per capita production, determining the composition and density of solid waste, and characterizing the amount and composition of the DSW generated by the samples taken from the San Sebastián del Coca parish. 48 families were chosen to carry out the research with an average of 4 inhabitants per family for a total of 192 people. As for the methodology, the simple random sampling method was used. A total of 96 dwellings samples that were obtained directly from the dwellings was chosen to be part of the study sample. The results showed that the generation of solid waste, in other words the PPC of domestic solid waste, was 0.87 kg/inhab/day. This is with a total of 167.04 kg/day, which were collected by collector trucks and disposed according to the ordinance of the canton. The characterization of domestic solid waste in the parish has organic waste located in the first place with 78.2%. Next was the generation of plastic bags with 6.19%. This, therefore, was followed by cardboard with 5%, plastic 7.7%, and paper with 2.99%.